Development of Digital Encyclopedia Fish Diversity in The Auction of Tuban Fish As A Contextual Based Teaching Material Supplement - Aulia, Innarotul; Susanti, R.; Rusilowati, Ani (Journal of Innovative Science Education)
The diversity of fish as an environmental potential found in Tuban Regency can be used as a supplement to contextual-based teaching materials which are packaged in the form of a digital encyclopedia. Smartphone owned by students can be used in learning biology. This study aims to 1) Study and describe the diversity of fish at TPI Bulu Bancar and Gelondonggede Tambakboyo Tuban, 2) Assess product characteristics, 3) Test product validity based on material and media, 4) Test product effectiveness in improving student learning outcomes , and 5) Testing the practicality of the product. This research belongs to Research and Development. Observation is used as the data collection methodology in obtained fish biodiversity. The development is in the form of an android-based digital encyclopedia which is then used as a supplement to teaching materials for biodiversity. The trial was conducted at SMAN 1 Bancar Tuban by taking control and experimental classes. The results showed 1) The diversity of fish species found in TPI Bulu Bancar and Gelondonggede Tambakboyo Tuban each consisted of 17 species and 23 species, 2) Product characteristics were developed in digital form containing material on biodiversity of fish, 3) Validity by material experts valid criteria and media experts with very valid criteria. 4) The effectiveness test is seen from the increase in cognitive learning outcomes. The digital encyclopedia of fish diversity can be used as a supplement to teaching materials on contextual-based biodiversity materials.